Does accountability undermine service delivery? The impact of devolving agriculture in Ghana - Resnick, Danielle (Springer, 2022)
In recent years, many developing countries have devolved services to locally elected governments. Although this may strengthen downwards accountability to citizens, does devolution improve service provision? Ghana began devolving agriculture in 2012 to its Metropolitan, Municipal, and District Assemblies (MMDAs). Drawing on an original survey with 80 District Directors of Agriculture and 960 households, as well as district-level budget data and interviews with national and local government stakeholders, this paper shows that agricultural expenditures and services have been negatively affected by the transition. The imperative of electoral accountability encourages assembly members to de-prioritize agriculture in the budget process in favor of more visible goods and services. Budget allocations, however, do reflect the preferences of local citizens, a majority of whom value using elections to sanction their district politicians. The findings indicate that devolution may increase accountability but result in sectoral trade-offs in service provision, which may undermine national policy objectives.